Single Nucleotide Recognition and Mutation Site Sequencing Based on a Barcode Assay and Rolling Circle Amplification - Linmin Zhong; Huiping Chen; Shuang Cao; Shanwen Hu (Biosensors)
Single nucleotide polymorphisms (SNPs) present significant challenges in microbial detection and treatment, further raising the demands on sequencing technologies. In response to these challenges, we have developed a novel barcode-based approach for highly sensitive single nucleotide recognition. This method leverages a dual-head folded complementary template probe in conjunction with DNA ligase to specifically identify the target base. Upon recognition, the system triggers rolling circle amplification (RCA) followed by the self-assembly of CdSe quantum dots onto polystyrene microspheres, enabling a single-particle fluorescence readout. This approach allows for precise base identification at individual loci, which are then analyzed using a bio-barcode array to screen for base changes across multiple sites. This method was applied to sequence a drug-resistant mutation site in Helicobacter pylori (H. pylori), demonstrating excellent accuracy and stability. Offering high precision, high sensitivity, and single nucleotide resolution, this approach shows great promise as a next-generation sequencing method.